Fouling Behaviour During Cross Flow Ultrafiltration of Cassava Starch Hydrolysate Using Polyacrylonitrile Membrane - Widiasa, I. N.; Wenten, I. G. (Journal of Applied Membrane Science & Technology, 2017)
Ultrafiltration (UF) is considered as a promising alternative to the traditional clarification techniques in the sugar industries. In this work, a hollow fiber UF membrane (polyacrylonitrile, MWCO 100 kDa) was used for clarification of cassava starch hydrolysate. The influence of various operating parameters, such as transmembrane pressure (TMP), cross flow velocity and pH hydrolysate on the membrane fouling was assessed. The results showed that TMP higher than 1.0 bar was not effective to improve flux. Increasing cross flow velocity was virtually effective to reduce permeate flux decline. The steady state flux, Jssincreased significantly when pH of the feed was adjusted to alkaline condition; however, this resulted in dark brown clarified glucose syrup. Operating at natural pH of 4.5, the membrane selectivity was close to 100%. Evaluation of hydraulic resistance indicated that concentration polarization and pore blocking were beyond approximately 50 and 40% of the total filtration resistance, respectively. Moreover, scanning electron microscopy showed that extensive fouling layer was deposited on the membrane surface. Finally, the developed cleaning procedure could restore membrane performance approximately 45% of its initial performance.